(untitled) (Al-Qamar, 2021)
Education plays a pivotal role in the economic and social development of any country. Only a balance Education sytem can develop a healthy society. After 1857, Muslims emerged in India with two parallel but different directions of education system. Dãrul Üloom Deoband and Aligarh education system. This difference divided education into religion (Deen) and the world (Duniya).According to Pakistan’s 2017-18 educational statistics, out of 3,05,763 educational institutions in the country, there are 62% government, 28% private, and 10% religious madrassas. These institutions differ from one another in terms of their curriculum, environment, medium of instruction and examination system. As a result of these different types of education systems, young people, having different mind sets and conflicting philosophies of life are emerging in the society. Earliest ending of this class difference in Pakistan is a big challenge. If we look at the glorious past of Islam, there was the knowledge of religion and the world at the same time and no difference among rich and poor for education. We can systematically achieve a uniform education system by introducing uniform curriculum, medium of instruction, teaching methods, environment and examination methods. The present government has taken the first step in this direction with a "Single National Curriculum" which can be expected to restore some degree of harmony in the society and pave way for the achievement of therest of the goals.